2015
DOI: 10.1212/nxi.0000000000000080
|View full text |Cite|
|
Sign up to set email alerts
|

P2Y12 expression and function in alternatively activated human microglia

Abstract: Objective:To investigate and measure the functional significance of altered P2Y12 expression in the context of human microglia activation.Methods:We performed in vitro and in situ experiments to measure how P2Y12 expression can influence disease-relevant functional properties of classically activated (M1) and alternatively activated (M2) human microglia in the inflamed brain.Results:We demonstrated that compared to resting and classically activated (M1) human microglia, P2Y12 expression is increased under alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
122
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(140 citation statements)
references
References 43 publications
9
122
1
1
Order By: Relevance
“…The uptake of double-stranded DNA can induce activation of TLRs. The purinergic receptor P2Y12 is a TGF-β-responsive molecule uniquely expressed on mouse and human microglia and not on perivascular macrophages or blood-derived monocytes (50), and is expressed predominantly in homeostatic-type microglia (87). ADP is the endogenous ligand of P2Y12, and homeostatic microglia have increased ligand-mediated calcium responses, which are blocked by selective P2Y12 antagonism (87).…”
Section: Immune Cells Involved In Neurodegenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…The uptake of double-stranded DNA can induce activation of TLRs. The purinergic receptor P2Y12 is a TGF-β-responsive molecule uniquely expressed on mouse and human microglia and not on perivascular macrophages or blood-derived monocytes (50), and is expressed predominantly in homeostatic-type microglia (87). ADP is the endogenous ligand of P2Y12, and homeostatic microglia have increased ligand-mediated calcium responses, which are blocked by selective P2Y12 antagonism (87).…”
Section: Immune Cells Involved In Neurodegenerationmentioning
confidence: 99%
“…The purinergic receptor P2Y12 is a TGF-β-responsive molecule uniquely expressed on mouse and human microglia and not on perivascular macrophages or blood-derived monocytes (50), and is expressed predominantly in homeostatic-type microglia (87). ADP is the endogenous ligand of P2Y12, and homeostatic microglia have increased ligand-mediated calcium responses, which are blocked by selective P2Y12 antagonism (87). that distinguish resident microglia from peripheral mononuclear cells/macrophages (50-52) include FSRSL, P2Y12, TMEM119, CX3CR1, Siglec-H, and the microRNAs miR-99a, miR-125-5p, and miR-342-3p, which are highly expressed in both mouse and human microglia (50,53).…”
Section: Immune Cells Involved In Neurodegenerationmentioning
confidence: 99%
“…Future evaluation of microglial gene expression in post-mortem brains of PD patients who died at different stages of disease may aid investigators to better define microglial phenotypes. It is becoming increasingly clear that in many diseases, microglia largely express complex gene expression signatures (Butovsky et al, 2014; Moore et al, 2015; Pisanu et al, 2014; Tang and Le, 2015), and mixed phenotypes most likely reflect a dynamic state or may be simply due to the presence of a heterogeneous population of microglia during disease. Until human studies can be conducted to evaluate the neuroinflammatory interaction with neurodegeneration and other histopathological hallmarks like Lewy Body formation, conclusions about these relationships will have to be drawn from animal models of the disease.…”
Section: Microglia In Parkinson’s Disease (Pd)mentioning
confidence: 99%
“…Tested by double-label immunofluorescence, P2Y12 and GS (a marker of SGCs) were colocalized in the SGCs of the SG. P2Y12 receptor activation in human microglia results in increased release of TNF-α and IL-6 [36], whereas P2Y12 inhibitors reduce the levels of TNF-α and C-reactive protein (CRP) [37]. The elevated GS in the SG in our study suggested that SGCs were activated by the nerve injury stimulation induced by T2DM.…”
Section: Discussionmentioning
confidence: 74%